Terrorist violence and the enrollment of psychology in predicting Muslim extremism: critical terrorism studies meets critical algorithm studies. Issue 2 (3rd April 2019) - Miller, Flagg
ABSTRACT: Discourse on terrorist violence has long facilitated an especially liberal form of securitisation. Originally evoked in reference to anarchists and communists, a rational consideration of terrorist violence, inaugurated by the concept, asks for deferred judgement about the nature of, or reasons behind, violence related to terror on the premise that state and international legal norms governing the legitimate use of violence fail to circumscribe the proper capacities of the state to regulate and explain terrorism. Where sovereign powers along with their military and civilian instruments of coercion are deemed unable to regulate violence effectively, analysts of terrorist violence and their readership are invited to consider and cultivate new sensibilities. Beginning in the 1980s, studies by psychologists found renewed urgency among a growing cadre of interdisciplinary terror experts who found religion, Islam especially, a key variable of analysis. I situate their contributions in a longer history of secular and racialising discourse about terrorist violence. Central to this history are practices of reading, translating, interpreting and archiving texts. Evidence for the argument is based on the analysis of an algorithm that allegedly predicts the likelihood of terrorist strikes by counting words spoken by al-Qaʿida leaders and correlating their frequency with over 30 psychological categories.